Characteristics of flow and salinity intrusion in the Mekong delta - Ngo The Khai; Suphat Vongvisessomjai; Gupta, Ashim Das; Tawachai Tingsanchali; Preecha Kamronrithisorn; The Government of Australia (Bangkok : Asian Institute of Technology, 1988)
Characteristics of flow velocity and salinity intrusion into the estuarine system are a problem of great important for development of Mekong river. During t he dry season, about 1.5 million hectares of fertile land suffer from the l ack of fresh water source. This study presents different methods for the data analyse, analytical solution for velocity field and salinity intrusion. The study formulates the expression for longitudinal dispersion coefficient of the estuary and applies the mathematical model of one-dimensional. unsteady salinity intrusion in the Mekong river estuary . The model results were calibrated with observed values at different stations along the four main branches of the Mekong river. In regard of the problem of downstream boundary salinity and upstream constant source discharge , it becomes an important step for prediction possibility of the model. It is found that the daily average river discharge is too small in comparison with tidal one. The strong influence of "temporary storage" on average values of water level and discharge, and also of discharge distribution . The magnitude of dispersion coefficient is very high due to extreme slope and large specific discharge of the Mekong river.
A thesis submitted in partial fulfilment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1988
Keywords: Saltwater encroachment; Mekong Delta